2017
DOI: 10.14260/jemds/2017/696
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Efficacy of Local Infiltration Analgesia and Epidural Analgesia in Patients Undergoing Total Knee Replacements

Abstract: BACKGROUNDAims-Multiple studies have been done regarding post-operative analgesia after knee surgeries including intravenous opioids, epidural analgesia and nerve blocks. Hence, we compared the efficacy of Local Infiltration Analgesia (LIA) technique over Epidural Analgesia (EA) technique in patients undergoing TKR surgeries. MATERIALS AND METHODS72 patients of either sex, aged > 50 years, belonging to ASA I to III, posted for unilateral TKR for varus deformity were randomised into two groups. Patients in Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, improvements in pain control deserve the greatest credit for the more rapid recoveries that are now being seen [5] . Arthrofibrosis and diminished range of movements are closely related to degree of post-operative pain [6] . Hence, pain control after total knee arthroplasty (TKA) is of prime importance in the immediate postoperative period for early rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, improvements in pain control deserve the greatest credit for the more rapid recoveries that are now being seen [5] . Arthrofibrosis and diminished range of movements are closely related to degree of post-operative pain [6] . Hence, pain control after total knee arthroplasty (TKA) is of prime importance in the immediate postoperative period for early rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, pain control after total knee arthroplasty (TKA) is of prime importance in the immediate postoperative period for early rehabilitation. LIA is a Technique for management of acute phase of postoperative pain, particularly after knee and hip surgery [7,8] . It was developed by Dr. Dennis Kerr and Dr. Lawrence Kohan in Sydney.…”
Section: Discussionmentioning
confidence: 99%
“…However, this surgery is potentially associated with a series of complications such as infection, implant loosening, thromboembolic disease, implant fracture and readmission. (10,11) Although, there are different studies evaluating the outcomes of total knee arthroplasty in the world, this topic has not been assessed in our region, Babol, northern Iran, yet and we do not have any data to see if total knee arthroplasty is associated with acceptable outcomes or not. Therefore, this study was performed with the aim of evaluating the outcomes of total knee arthroplasty in Babol.…”
mentioning
confidence: 98%
“…Others included joint dislocation, bone fractures and prosthesis, deep venous thrombosis, nerve injury and remained pain. (8)(9)(10) It was reported that some factors can affect the surgery outcomes including demographic (Age, sex, ethnicity), social behaviours (Occupation, smoking, exercise), associated disease (Rheumatoid arthritis, diabetes) and place of health service reception (Governmental/ Private hospitals, trainings after the discharge). (11,12) Considering the increasing trend in total hip and knee replacements and the serious post-operative complications and also given the limited information on the outcomes of the two surgeries in Iran, we aimed to assess the results of the total hip and knee arthroplasty and the related factors in north of Iran.…”
mentioning
confidence: 99%